2009
DOI: 10.1016/j.lwt.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Brazilian vinegars according to their 1H NMR spectra by pattern recognition analysis

Abstract: 1 H NMR SIMCA KNN PLS-DA a b s t r a c tThis work describes using 1 H NMR data and pattern recognition analysis to classify vinegars. Vinegar authenticity is linked to raw ingredient source and manufacturing conditions. Application of PCA and HCA methods resulted in the natural clustering of the samples according to the raw material used. Wine vinegars were characterized by a high concentration of ethyl acetate, glycerol, methanol and tartaric acid, while glycerol and ethyl acetate signals were not visible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…3-5). Signals identification was further supported by molecular attribution reported in literature for wine 1 H NMR spectra [13,14,16,21,24]. Most of the above compounds are mainly of microbial origin: lactic acid is the metabolic product of malo-lactic fermentation performed by malo-lactic bacteria (MLB) [25]; succinic acid is the major organic acid produced by yeast metabolism [26]; glycerol is the final product of glyceropiruvic fermentation by yeast and its formation accompanies ethanol production in sugar fermentation [27].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…3-5). Signals identification was further supported by molecular attribution reported in literature for wine 1 H NMR spectra [13,14,16,21,24]. Most of the above compounds are mainly of microbial origin: lactic acid is the metabolic product of malo-lactic fermentation performed by malo-lactic bacteria (MLB) [25]; succinic acid is the major organic acid produced by yeast metabolism [26]; glycerol is the final product of glyceropiruvic fermentation by yeast and its formation accompanies ethanol production in sugar fermentation [27].…”
Section: Resultsmentioning
confidence: 72%
“…In fact, it was observed that application of a 3 s delay between initial 180 • and second 90 • hard pulse, efficiently suppressed the ethanol multiplets and acetic acid singlet at 2.09 ppm [13,21], while it allowed recovering all other signals without significant intensity loss. In addition, this pulse sequence included a water signal pre-saturation, that resulted in a concomitant removal of both undesired water and ethanol signals ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This electromagnetic technique requires sensors with highly sophisticated mathematical models and computer software algorithms that can be harnessed to relate physical or chemical properties and quality attributes of the product in consideration. The combination of PLS-DA and NMR has been successfully used to detect adulterants in several foodstuffs including cereals and cereal products (Boffo et al, 2009;Marcone et al, 2013). PLS-DA is a widely used multivariate technique that uses few latent variables, takes into account the correlation between the variables, filters the noise, and leads to good predictive performance of the model.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…At present, the fingerprint technique has become one of people's research hotspots, and there have been some very good research reports. The reports include organic mass spectrum [6][7][8][9], inorganic element [10][11][12][13], biochemistry [14][15][16], HPLC [17,18], GC [18][19][20], CE [21], NMR [7,22], UV [7,23] and IR fingerprints [23][24][25][26][27][28][29], etc. Among the techniques, the application research of chromatographic fingerprint are the most prevalent and in-depth due to its traits of qualitative, quantitative and multidimensional information, and has been used in the fingerprint analyses of extraction solution and volatile components of samples.…”
Section: Introductionmentioning
confidence: 99%